Reviews on Technology and Standard of Spatial Audio Coding - Luthfi, Amirul; Elfitri, Ikhwana (Jurusan Teknik Elektro Universitas Andalas, 2017)
Market demands on a more impressive entertainment media have motivated for delivery of three dimensional (3D) audio content to home consumers through Ultra High Definition TV (UHDTV), the next generation of TV broadcasting, where spatial audio coding plays fundamental role. This paper reviews fundamental concept on spatial audio coding which includes technology, standard, and application. Basic principle of object-based audio reproduction system will also be elaborated, compared to the traditional channel-based system, to provide good understanding on this popular interactive audio reproduction system which gives end users flexibility to render their own preferred audio composition.Keywords : spatial audio, audio coding, multi-channel audio signals, MPEG standard, object-based audio